Pengaruh Mobilisasi Dini Pasien Post Sectio Caesarea Terhadap Gangguan Mobilitas Fisik Di Puskesmas Danau Paris Kabupaten Aceh Singkil Tahun 2024 - Lisa Putri Utami Damanik; Afni Veronika Tambunan; Herna Rinayanti Manurung; Siti Nurmawan Sinaga; Zulkarnain Batu Bara; Magdalena Barus (Inovasi Kesehatan Global, 2024)
Background: Sectio Caesarea (SC) is a surgical procedure to deliver a fetus by making an incision to open the abdominal wall and uterine wall or a hysterotomy to remove the fetus in the mother's womb. In recent years, normal delivery has been considered a difficult way of giving birth and tends to be dangerous for the mother and her baby. The use of Caesarean section is increasing globally, and now accounts for > 1 in 5 (21%) of all births. This number is predicted to continue to increase, almost a third (29%) of all births are estimated to be carried out via sectio in 2030. Method: This type of research is quantitative with a quasi-experimental approach. The research was conducted at the Lake Paris Health Center, Aceh Singkil Regency in 2024. The research population was all post partum mothers with cesarean sections at the Lake Paris Health Center, Aceh Singkil Regency, namely 30 people. The sampling technique used was simple random sampling. The data analysis used was univariate analysis and bivariate analysis, the analysis used was the Non-Parametric Test (Man-Whitney) with α = 0.05. Results: The results of the study showed that before the intervention was carried out, there were 3 respondents experiencing mild pain (10.0%), 14 respondents experienced Moderate pain (46.7%), and 13 respondents experienced severe pain (43.3%). After the intervention, 2 experienced no pain (6.7%), 13 experienced mild pain (43.3%), 2 experienced moderate pain (6.7%), 13 experienced severe pain (43.3%). Conclusion: The results of statistical tests obtained P value = 0.000 < 0.05, meaning that there was a significant difference before and after giving early mobilization treatment to mothers post cesarean section at the Lake Paris Health Center, Aceh Singkil Regency in 2024